Psycho-pedagogical Counseling in the Age of Digitalization and the Ecosystem of Well-being - Musunoiu-Hoton, Violeta-Luminita (Didactica Danubiensis, 2022)
General well-being and active involvement of school counsellors online can be achieved through psycho-pedagogical assistance, using modern technologies. The Collins Dictionary defines “digitalization as “a period in which large quantities of information are available on a large scale for a wide variety of people, mostly through computer technology”.